HUKUM KEWARISAN MENURUT KOMPILASI HUKUM ISLAM (HKI) DAN KEWARISAN MENURUT MAZHAB SYAFI’I (KAJIAN PERBANDINGAN) - Abdul Rahim (IAI Al-Mawaddah Warrahmah Kolaka, 2018)
The study discusses the comparisons of the Islamic Law Compilation (KHI) which is the applied law and guidelines by its major government agencies in the Religious Courts with the heritage of the Syafi'i school which is just as doctrines in filling the vacancy (rectsvaacum) against Islamic Law Compilation (KHI) normative, Compilations of Islamic Law (KHI) have not addressed all the problems in the law of inheritance. For that, it is still necessary to conduct a joint assessment of the two. In an effort to comprehend the law of Islamic heritage comprehensively, understanding the fundamental concepts of Islamic heritage law and its theories (inscontituendum) and the Islamic law of law that apply as a positive law in Indonesia (iusconstitutum). This research type is a legal research. The comparative juridical approach, which is comparative with Mazhab, compares between the two legal systems of inheritance in KHI and inheritance according to Imam Shafi'i. Which law comparison is done to determine how the equality side and the side of the difference between two or more of a different legal system . From the results of the study the fact that both theories classify the heirs of the three classes, recognize the rad, know the hijab, maintain the share of inheritance 2: 1 The difference is, among others, KHI and Shafi'i differentiate the meaning of Al-Nisa's verses 11 and 12 both in terms of the heir status and the provisions for heirs. Against rad, successor heirs, wills and grants as well as some other things, both theories also differ. The advantages and disadvantages of each theory lie in those differences. Special KHI inheritance, its setting is too simple and hesitant in determining the size of a replacement heir. This certainly impacts legal certainty.